Menegosiasi Otentisitas: Kancah Musik Independen Indonesia dalam Konteks Komodifikasi oleh Perusahaan Rokok - Bagaskara, Adam (UI Scholars Hub, 2017)
The Intrusion of big businesses into the Indonesian independent music scene does not harm the authenticity of musicians’ working position as their creative autonomy can still be maintained. It is important to maintain creative autonomy to assure that the songs produced by independent musicians reflect the social-political nature of the society, thus representing the quality of high culture. The commodification of Indonesian independent music scene by tobacco companies is an interesting phenomenon to be explored as it contradicts the ideological scheme of independent music scenes – The Do It Yourself (DIY) attitude. The scene actors compromise in the musical scene to obtain material necessity. Hence, this phenomenon follows Hermondhalgh’s argument on Cultural Commodification. This article is written based on a qualitative research applying an in-depth interview to obtain information from Indonesia independent music actors.